Assessing the legal and political implications of the post-Cotonou negotiations for the Economic Partnership Agreements - Niels Keijzer; Lorand Bartels (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The role of the Cotonou Agreement during the negotiation of Economic Partnership Agreements (EPAs) between the European Union (EU) and the African, Caribbean and Pacific (ACP) Group of States has been well studied. This paper analyses the inverse of this relationship, namely the legal and political implications of different possible outcomes of the upcoming post-Cotonou negotiations on the EPAs, following the expiry of the Cotonou Agreement in 2020. The EPAs include several cross-references to provisions in the Cotonou Agreement on development and human rights. This paper analyses the legal and political implications for the EPAs of possible negotiation outcomes, including combinations of regional or non-legally binding cooperation agreements. Its main conclusion is that a decision not to renew the Cotonou Agreement would have significant political implications but, contrary to the views of some EU stakeholders, limited legal implications for the EPAs.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Handel und Investitionen